Searching for puma-rancher coexistence in central Argentina - Lucherini, Mauro (2024)
The puma (Puma concolor) is listed as Least Concern in Argentina but in many areas its populations are threatened by habitat loss and hunting. This is the case for central Argentina, a region that was once occupied by natural grasslands and xeric woodlands and that has been largely transformed by expansion of the agriculture frontier. These transformations also led to increased proximity between pumas and livestock. When natural prey became less available than domestic animals, pumas began preying on livestock, particularly sheep (Fig.1). The human response was retaliatory and preventive killing (Fig. 2), which brought local puma populations close to extirpation in the second half of last century. More recently, economic changes and some severe droughts led to abandonment of farms and recovery of puma populations, which, in turn, caused intensification of puma-livestock conflicts. Although Buenos Aires province government forbids puma hunting, it does not manage conflict ,and retaliatory killing of pumas and Pampas foxes (Lycalopex gymnocercus), a canid also blamed for preying on lambs, is extremely common and socially accepted. In fact, in other neighboring provinces, puma and fox hunting is allowed and encouraged by a bounty system.